Idecabtagene vicleucel in relapsed and refractory multiple myeloma - Munshi, Nikhil C.; Larry D. Anderson, Jr; Shah, Nina; Madduri, Deepu; Berdeja, Jesús; Lonial, Sagar; Raje, Noopur; Lin, Yi; Siegel, David; Oriol, Albert; Moreau, Philippe; Yakoub-Agha, Ibrahim; et al. (The New England journal of medicine, 2021)
Original Article from The New England Journal of Medicine — Idecabtagene Vicleucel in Relapsed and Refractory Multiple Myeloma
Gesehen am 13.04.2021